Facile One-Step Electrodeposition Preparation of Cationic Pillar[6]arene-Modified Graphene Films on Glassy Carbon Electrodes for Enhanced Electrochemical Performance - Duan, Qunpeng; Wang, Lijie; Wang, Fei; Zhang, Hongsong; Lu, Kui (Frontiers in Chemistry, 2020)
In the present work, we have developed a facile one-step route for preparing electrochemically reduced graphene oxide-cationic pillar[6]arene (ErGO-CP6) nanocomposite films on glassy carbon electrode (GCE) directly from graphene oxide-cationic pillar[6]arene (GO-CP6) colloidal solution by pulsed electrodeposition technique. The electrocatalytic activity of ErGO-CP6 was examined by studying the oxidations of five purine bases [adenine (A), guanine (G), xanthine (X), hypoxanthine (HX) and uric acid (UA)]. It enhanced the oxidation currents of A, G, X, HX, and UA when compared to unmodified ErGO films and bare GCE, which is considered to be the synergetic effects of the graphene (excellent electrical properties and large surface area) and CP6 molecules (high inclusion complexation and enrichment capability).